Interactions of Trivalent Lanthanide Cations with a New Hexadentate Di-Schiff Base: New Lanthanide(III) Complexes from (NE, N′E)-2, 2′-(ethane-1, 2-diylbis(oxy))bis(N-(pyridin-2-ylmethylene)ethanamine). (22nd June 2010) - Tsiouri, Mantha; Skorda, Konstantina; Papadimitriou, Christos; Li, Yang; Woollins, J. Derek; Plakatouras, John C.
Abstract : The novel lanthanide(III) complexes [ Ln ( NO 3 ) 2 L ] ( NO 3 ) ⋅ 3MeOH (Ln = La 1, Pr 2 ) and [ Ln ( NO 3 ) 3 L ] ( NO 3 ) ⋅ 2MeOH (Ln = Gd 3, Yb 4 ), where L = (NE, N ′ E)-2, 2 ′ -(ethane-1, 2-diylbis(oxy))bis(N-(pyridin-2-ylmethylene)ethanamine), have been obtained by direct reaction of the Schiff base ligand and the corresponding hydrated lanthanide(III) nitrates in methanol. All complexes were characterized spectroscopically and thermogravimetrically. Complex 4 was also characterized with crystallographic studies: orthorhombic P2 1 2 1 2 1, a = 10.6683 (14), b = 13.4752 (15), c = 19.3320 (26) Å. In the molecular structure of 4, Yb(III) is surrounded by all donor atoms of the Schiff base (four nitrogen and two oxygen atoms) and four oxygen atoms belonging to two bidentate chelating nitrato ligands.